A conceptual approach to practitioners' health information literacy. Issue 2 (13th June 2016) - Hallyburton, Ann
Abstract : Purpose: The purpose of this paper is to examine healthcare professionals' own health literacy through the lenses of information behavior and evidence-based practice. These practitioners' health information literacy is critical to client care. Design/methodology/approach: This conceptual paper applies general and professional-specific models of information behavior and issues of bias to methods in which healthcare practitioners seek, evaluate and use research information within professional practice. Findings: Case examples from library, medical and the broader healthcare literature are used to explore ways in which care professionals' information behaviors align with or deviate from information behavior models and the role of different types of bias in their information behavior. Adaption of evidence-based practice precepts, already familiar to healthcare professionals, is proposed as a method to improve practitioners' health information literacy. Originality/value: Explorations of "health literacy" have primarily focused on healthcare consumers' interactions with basic health information and services. The health literacy (and health information literacy) of care practitioners has received much less attention. By gaining a greater understanding of how information behaviors intersect with healthcare practitioners' own health literacy, the librarians and educators who serve future and current care professionals can offer more informed information literacy instruction, enabling practitioners to provide improved patient care.